EMOTIONAL-EXPRESSIVE STUDY OF WORDS RELATED TO THE WORD “LAUGHTER” IN WORLD LINGUISTICS - Ulugbek Rahmonov (Journal Park Publishing, 2022)
The article focuses on the analysis of emotional words related to the word “Laughter”. It analyzes the meanings given in Uzbek and English explanatory dictionaries and translation dictionaries.
Keywords: Laughter, emotion, expressiveness, to giggle, to titter.